Contrasting processes driving tropical and non-tropical winter warm spells - Sijia Wu; Ming Luo; Manqing Shi; Yu Tang; Tuantuan Zhang; Qiuting Wang; Xiaoyu Wang (Communications Earth & Environment)
Abstract Winter warm spells (or winter heatwaves) are prolonged periods of anomalously high temperatures in cold seasons where hot weather typically does not occur. These off-season events challenge ecosystems and societies by triggering snowmelt-induced flooding and favoring wildfires, etc., but are yet to be understood. Here we assess the behaviors and drivers of worldwide winter warm spells, which have become more frequent and longer-lasting during 1979–2023. Net shortwave and longwave radiations induced diabatic heating predominantly contribute to temperature anomalies during winter warm spells, but their contributions exhibit contrasts between the tropics and non-tropics. Specifically, tropical winter warm spells are primarily induced by increased solar radiation, accompanied by decreased cloud cover, dried soils and atmosphere, and moisture divergence; whereas, non-tropical winter warm spells are mainly driven by enhanced downwelling longwave radiation under cloudier and wetter conditions. Our findings underscore the urgency to understand and mitigate intensifying off-season events that occur outside their typical seasons in a warming world.